Analysis of combined electroosmotic dewatering and mechanical expression operation for enhancement of dewatering - Iwata, Masashi; Jami, Mohammed Saedi (Taylor & Francis, 2010)
This article presents an efficient approach for the analysis of combined electroosmotic dewatering (EOD) and mechanical expression (ME) using the Terzaghi-Voigt combined model by considering creep deformation of the material. The EOD-ME process enhances dewatering because it combines the advantage of electroosmosis and mechanical dewatering, resulting in reduced void ratio compared to individual operation. The basic differential equation based on the model is solved analytically by assuming that both an electroosmotic pressure gradient Epg and a modified consolidation coefficient Ce of the material are constant, resulting in the equation of solid compressive pressure in the material as a function of time and position. The analysis also leads to the equation of the average consolidation ratio Uc, which is a measure of the progress of dewatering; this equation can describe well the empirical results under various conditions. The proposed approach can clearly explain the relationship of the driving forces of individual mode of operation. The large water content of semisolid bentonite–water mixture can effectively be reduced by the EOD-ME combined operation analyzed in this research.